Omitting vitamin and trace mineral premixes, and(or) reducing inorganic phosphorus during late finishing did not affect growth performance, carcass traits, or muscle quality - I Mavromichalis; Donald H Kropf; G A Kennedy; Robert H Hines; B W Senne; I H Kim; S L Johnston; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1996)
Omitting the vitamin and trace mineral premixes and(or) adding 2/3 less supplemental inorganic phosphorus source (from .55% down to .40% total P) to diets during late finishing (191 to 265 lb) had no effect on growth performance, carcass characteristics, or muscle quality in high-lean pigs. Thus, this concept can be used to decrease the cost of feeding terminal-cross pigs to heavy weights, while decreasing excretion of minerals from intensive swine operations.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Finishing pigs; Vitamins; Minerals; Phosphorus; Meat quality